Aplikasi Konsep Tropis pada Restoran dan Retail di Bojonegoro - Kurniawati, Dessy (Intra, 2017)
As a developing city, Bojonegoro requires innovation in commercial needs. This interior design aims to answer the problems of the community who require facilities for eating, drinking and retailing. In fact, people need a new atmosphere to relax. Therefore, the application of the concept of